The World of Algae Reveals a Broad Variety of Cryptochrome Properties and Functions - Petersen, Jan; Rredhi, Anxhela; Szyttenholm, Julie; Oldemeyer, Sabine; Kottke, Tilman; Mittag, Maria (Frontiers in Plant Science, 2021)
Algae are photosynthetic eukaryotic (micro-)organisms, lacking roots, leaves, and other organs that are typical for land plants. They live in freshwater, marine or terrestrial habitats. Together with the cyanobacteria they contribute to about half of global carbon fixation. As primary producers, they are at the basis of many food webs and they are involved in biogeochemical processes. Algae are evolutionarily distinct and are derived either by primary (e.g. green and red algae) or secondary endosymbiosis (e.g. diatoms, dinoflagellates, brown algae). Light is a key abiotic factor needed to maintain the fitness of algae as it delivers energy for photosynthesis, regulates algal cell- and life cycles and entrains their biological clocks. However, excess light can also be harmful, especially in the ultraviolet range. Among the variety of receptors perceiving light information, the cryptochromes originally evolved as UV-A and blue light receptors and have been found in all studied algal genomes so far. Yet, the classification, biophysical properties, wavelength range of absorbance and biological functions of cryptochromes are remarkably diverse among algal species, especially when compared to cryptochromes from land plants or animals.